Identifikasi Masalah Menggunakan Teknik Problem Check-List Pada Siswa SMA Negeri 1 Baros - Al Jabbar, Brama; Eilen Ardi Estiningtyas; Siti Nurhalisah; Mohammad Jaelani; Sri Hartati; Sarah Azzukhruf; Akhmad Vikry; Putri Fauziah; Sabrina; Alfiandy Warih Handoyo (PT. Gudang Pustaka Cendekia, 2023)
Guidance and counseling is a service provided by schools, one of the functions of which is to help students identify various kinds of problems inherent in them in order to realize effective learning. The various problems faced by students in classes towards the school, adjustments to the curriculum, study habits as well as the future and aspirations obtained from the Problem Checklist filled in by students. The research was conducted using descriptive quantitative research with a sample of 109 students using the Slovin formula. The research results were analyzed using percentages and produced findings that the problems faced by students were very diverse, thus hindering the learning process.